Peranan Bank Pembangunan Daerah Dalam Sosialisasi Dan Edukasi Mahasiswa Tentang Kemanfaatan Produk Dan Jasa Perbankan - Elsyan Rienette Marlisa (UNIVERSITAS CENDERAWASIH, 2019)
The main objective of this community engagement namely to identify and understand banking products and services that Bank Papua offers to the community. Meanwhile, the information related to Products of banking can be obtained through lecture at the Economics Department in relation to the types of banking products and the objectives of them or the similar information also can be gain from marketing person from Bank Papua who capable enough to explain in detail about banking products and services. According to the outcome of this activity that had been conducted to the Economics’ Students from Faculty of Economics and Business at Cenderawasih University, can be concluded as follow: In order to distribute fund, the conventional banks will distribute it through deposits and savings to the public in form of loans, as well as in form of financing for the Islamic Banks. In addition, the loan from conventional banks in distributing process will subject to interest and other loan services in the form of administrative fees, and commission fees. Whereas Islamic banks are based on buying and selling and profit sharing; in order to provide in depth meaning of Bank Papua products and services, a film screening by Bank Papua Speakers had been played, and the key speaker from Marketing Division of Bank Papua has given a talk about Bank Papua products and services namely electricity payment, telephone payment, tuition fee, transfer service, and others. This activity has relevance to the Economics students that they have been introduced during their study in university in the subject of Monetary Economics I & II during Semester II & III and other subject such as Banks and Financial Institution on (V Semester) as well as Monetary Policy in Development sector (VII Semester). Therefore, the outcome of this activity that could motivate students to recognize the characteristics of Bank Papua products and services as well as can differentiate between genuine and counterfeit money.